1991
DOI: 10.1111/j.0022-3646.1991.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

DENSITY‐DEPENDENT GROWTH, ECOLOGICAL STRATEGIES, AND EFFECTS OF NUTRIENTS AND SHADING ON BENTHIC DIATOM SUCCESSION IN STREAMS1

Abstract: The importance of immigration, growth, and competition for nutrients and light in benthic diatom succession was studied in experimental channels in a low‐nutrient stream. Diatom accumulation was greater in channels enriched with nitrate and phosphate (NP) than in control channels, reaching about 5 × 106 and 2 × 106 cells‐cm−2, respectively, after 30 d. Shading during late stages of community development reduced algal standing crop. Synedra ulna (Nitz.) Ehr. and Achnanthes minutissima Kütz. were codominant dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(77 citation statements)
references
References 53 publications
4
70
0
3
Order By: Relevance
“…This observation conforms with expectations of the Intermediate Productivity Hypothesis, predicting higher taxonomic richness at higher (but not extreme) levels of growth-limiting resources such as nutrients, space or light (Grime 1979;Waide et al 1999). Several experimental studies using periphyton have also shown that successional rates increase with higher nutrient supply (e.g., Pringle 1990;Stevenson et al 1991). Moreover, Pringle (1990) found higher taxon richness of periphyton in enriched waters than in unenriched waters.…”
Section: Chlorophyll Biomasssupporting
confidence: 85%
“…This observation conforms with expectations of the Intermediate Productivity Hypothesis, predicting higher taxonomic richness at higher (but not extreme) levels of growth-limiting resources such as nutrients, space or light (Grime 1979;Waide et al 1999). Several experimental studies using periphyton have also shown that successional rates increase with higher nutrient supply (e.g., Pringle 1990;Stevenson et al 1991). Moreover, Pringle (1990) found higher taxon richness of periphyton in enriched waters than in unenriched waters.…”
Section: Chlorophyll Biomasssupporting
confidence: 85%
“…The adnate life form encompasses the mobile and most of the low-profile diatoms. They are fast-growing species which could be favoured at high levels of nitrate because of nutrient stimulation but are less competitive in dense mature biofilms (Stevenson et al, 1991). Stalked diatoms appear to have an advantage when NO 3 À levels are low, meanwhile adnate diatoms could profit from decreased competition from stalked diatoms when NO 3 À levels are high.…”
Section: Discussionmentioning
confidence: 99%
“…At the upstream site, mainly during the high water period, floods may have caused sloughing of life forms from the outer layers of the biofilm, thus resetting the algal community to early successional stages, as in Oemke and Burton (1986), Peterson and Stevenson (1992) and Peterson (1996). McCormick and Stevenson (1991) and Stevenson et al (1991) proposed that, during succession, benthic algal dominance change from species with high immigration abilities or disturbance resistant, such as Cocconeis spp., to species that predominate with limiting resources and high population densities, such as stalked species. In lotic ecosystems, where the spatial heterogeneity shaped by the current maintains a patch dynamics (Townsend, 1989) and temporal variation in the discharge produces periodical disturbances, the life forms of early and late-successional species represent ecological viable strategies.…”
Section: Discussionmentioning
confidence: 99%